Fruits basket. 12 - Takaya, Natsuki, 1973- (Yen Press, 2017)
Their curse might be broken, but big questions still lie ahead for the Sohma family. Now that Kyo is free to dream of his future, what will he make of it? Does growing up mean growing apart, or will his bond with Tohru only strengthen with time? Perhaps their first date will decide And at long last, the meaning of Kyoko's ominous words "I'll never forgive you" becomes clear.